Pengaruh Kualitas Pelayanan Dan Store Atmosphere Terhadap Kepuasan Konsumen Pada Cafe Mp Di Desa Brenggolo - Dimas Didik Pramudia; Ahmad Jauhari; Beny Mahyudi Saputra (STIKes Ibnu Sina Ajibarang, 2023)
In the current era of globalization, there is intense competition in the business world. Business actors are required to create competitive advantages based on the quality of service and atmosphere in their businesses and strive to provide consumer satisfaction to face business competition. This research aims to determine the results of the influence of service quality, store atmosphere, and consumer satisfaction at Cafe MP in Brenggolo Village. The method used in this research is a quantitative method. The sampling technique in this research is the accidental sampling method. The number of samples in this research was 85 consumers. Data collection techniques include observation, interviews, questionnaires and literature studies, with the help of IBM SPSS version 25. The research results show that Service Quality has a significant (partial) influence on consumer satisfaction, the result value is 8.222 and the significance value is 0.025 <0.05. Store Atmosphere has a significant (partial) influence on consumer satisfaction, a result value of 9.622 and a significance value of 0.000 <0.05. Service quality and Store Atmosphere influence (simultaneously) on consumer satisfaction at MP Cafe in Brenggolo Village, the f test value is 97.549 and the significance value is 0.000 <0.05.